Pengaruh Literasi Keuangan Dan Penggunaan Media Sosial Terhadap Kinerja UMKM - Aulia, Elvira Frischa; Mariska, Revi Sasti; Suseno, Novie Susanti (LPPM POLITEKNIK LP3I BANDUNG, 2025)
Our main objective in conducting this research is to identify the relationship between MSME performance and the level of financial literacy and social media usage in Garut Regency. The purpose of this study is to help MSMEs, which in turn will help the economy, the labor market, and the field of management and economic theory. The sample for this study consists of all micro, small, and medium enterprises (MSMEs) in Garut Regency, which is 45 samples. The author used a questionnaire to collect information directly from the MSME players in Garut Regency. After collecting data through surveys and literature studies, the author analyzed it using multiple linear regression and the coefficient of determination. Quantitative methods were used in this study. Based on the research results, there is an influence between financial literacy and the success of micro, small, and medium enterprises (MSMEs). Micro, small, and medium enterprises (MSMEs) tend to do better when their owners are financially literate and active on social media.